2017
DOI: 10.14202/vetworld.2017.973-978
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteriophages with lytic activity against common bacterial pathogens

Abstract: Aim:Present investigation was conducted to isolate and characterize bacteriophages with lytic activity against common bacterial pathogens.Materials and Methods:A total of 60 samples of animal waste disposal from cattle (42) and buffalo (18) farms were collected from three different strata, i.e., top, mid, and bottom of collection tank. Samples were primarily subjected to rapid detection methods, and then isolation of phage was done by double agar layer method using Bacillus subtilis (BsH) and Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 23 publications
9
32
0
2
Order By: Relevance
“…Both UPEC04 and UPEC10 were stable to heat up to 60℃. At 70℃, the phages were inactivated which is in agreement with Lu et al (2003) and Shende et al (2017) who reported that phages get inactivated at 70℃ and above [51,53].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both UPEC04 and UPEC10 were stable to heat up to 60℃. At 70℃, the phages were inactivated which is in agreement with Lu et al (2003) and Shende et al (2017) who reported that phages get inactivated at 70℃ and above [51,53].…”
Section: Discussionsupporting
confidence: 88%
“…The main physical factors affecting phage adsorption and growth include pH and temperature [53]. The different pH and temperature ranges in this study were selected to mimic those that would be encountered during the handling and application of these phages as therapeutic or sanitizing bio-control agents on poultry farms.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Shende et al (2017), fagos com amplitude de hospedeiro do tipo polivalente possuem potencial para substituir os antibióticos, e os fagosPedr3Sa, Pedr3Ec e Pedr3Pa apresentaram amplitude deste tipo, porém, deve ser considerado que a investigação de fagos com o intuito de Tabela 1. Características morfológicas do ensaio de placa.…”
Section: Resultsunclassified
“…One-step growth experiments were carried out by a modification of methods described elsewhere [27,28].The logarithmic phase mixed with an overdose of phage host (MOI 10), 37 ℃ warm bath after 15 min 12000 rpm centrifugal 1 min, discard supernatant and wash with LB to precipitate .Then, suspended in LB that had been pre-warmed to 37 °C, followed by incubation at 37 °C. Samples were taken at 10 min intervals (up to 90min) and immediately diluted, and phage titers were then determined by double-layered agar plate method.…”
Section: One-step Growthmentioning
confidence: 99%